PENTINGNYA PEMBELAJARAN HADITS DALAM PERKEMBANGAN MORAL ANAK - Sitorus, Nurazizah; Nasution, Siti Salimah; Windira, Nurul; Jumiarni, Siti Fatonah Try; Hajni, Jahara Juniarti; Fristi, Adinda (Proceeding International Seminar of Islamic Studies, 2024)
Character education is a very important issue in the world of education. Moral belief education is one solution that can be given to young children in developing character education from an early age. method by collecting data by understanding and studying theories from various literature related to the research. In this character education, the role of parents is the most important, especially mothers. The Qur'an clearly describes the role of mothers in caring for children from birth, breastfeeding until weaning.